2020
DOI: 10.2174/1871530319666190809150921
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of Renin Angiotensin System Ameliorates the Cardiac Arrhythmias and Sympathetic Neural Remodeling in Hearts of Type 2 DM Rat Model

Abstract: Objectives:: The present study was designed to investigate the effects of renin angiotensin system (RAS) blockade on cardiac arrhythmias and sympathetic nerve remodelling in heart tissues of type 2 diabetic rats. Methods:: Thirty-two male Sprague Dawley rats were randomly allocated into 4 equal groups; a) normal control group: normal rats, b) DM group; after type 2 diabetes induction, rats received 2ml oral saline daily for 4 weeks, c) DM+ ACEi: after type 2 diabetes induction, rats were treated with enalapr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
1
4
0
Order By: Relevance
“…Also, Bakovic et al [46] demonstrated that the increased sympathetic nerve fiber density in diabetic hearts started 2 weeks after induction of DM and reaching its peak after 2 months, then declined 6 to 12 months after DM induction. Also, a recent study by Hussein and colleagues demonstrated similar findings [9]. Moreover, we found in the current work a significant reduction in TH density and myocardial NE contents by either SGLT2i or GLP1, suggesting attenuation of the sympathetic nerve fiber activity is another possible mechanism for the cardioprotective effects of these new antidiabetic agents in DCM.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Also, Bakovic et al [46] demonstrated that the increased sympathetic nerve fiber density in diabetic hearts started 2 weeks after induction of DM and reaching its peak after 2 months, then declined 6 to 12 months after DM induction. Also, a recent study by Hussein and colleagues demonstrated similar findings [9]. Moreover, we found in the current work a significant reduction in TH density and myocardial NE contents by either SGLT2i or GLP1, suggesting attenuation of the sympathetic nerve fiber activity is another possible mechanism for the cardioprotective effects of these new antidiabetic agents in DCM.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, strategies aiming to modulate fibrosis, inflammation, apoptosis and oxidative stress could be effective in management of DCM. Also, a recent study reported a significant increase in sympathetic nerve endings density (by measuring tyrosine hydroxylase activity) in the hearts of type 2 diabetic rats [9].…”
Section: Introductionmentioning
confidence: 94%
“…Of note, besides the direct myocardial structural damages (i.e., ischemia, necrosis, fibrosis, hypertrophy, disarray, etc.) [ 5 , 6 ], drugs [ 7 , 8 , 9 ], aging [ 9 , 10 , 11 , 12 ], mental stress [ 13 , 14 , 15 ] and neurohumoral activation [ 4 , 10 , 12 , 16 , 17 , 18 , 19 , 20 , 21 ], as well as the immune–inflammatory response [ 22 , 23 ] are all factors able to worsen the myocardial repolarization phase. Thus, due to the abovementioned high susceptibility to different possible stressors, there is growing interest in the analysis of myocardial repolarization phase dispersion as a possible marker of global cardiovascular risk rather than a mere non-invasive electrophysiological marker of electrical instability.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the density and number of sympathetic nerve fibers are significantly increased in diabetic hearts, suggesting overactivation of sympathetic nerves playing an important role in DCM. 131,132 Overactivation of the sympathetic nervous system promotes cardiac hypertrophy, fibrosis, cardiomyocyte apoptosis, and cardiac dysfunction. 133 Dapagliflozin decreases tyrosinehydroxylase density and myocardial norepinephrine content, contributing to attenuation of myocardial damage and fibrosis, indicating that improved sympathetic nerve activity is a potential mechanism for the cardiac protection of SGLT2Is in DCM.…”
Section: Othersmentioning
confidence: 99%